Promoting Vietnamese Cultural Values in the Current Context - Pham Ngoc Tram (MultiTech Publisher, 2024)
Promoting Vietnamese cultural values in the current context is important for preserving national identity and fostering sustainable development. In globalization and cultural exchange, actively and effectively promoting traditional cultural values is essential. Vietnamese culture is the soul of the nation, an undying vitality, and the source of strength that enables our people to stand firm and resilient in the face of all difficulties, natural disasters, wars, and eras. Vietnamese culture is both a product and a driving force in our nation's efforts to protect its sovereignty and resist invasions throughout thousands of years of history. Enhancing the value of cultural preservation is of immense importance in the new era. This article clarifies the distinctive values and significance of Vietnamese cultural preservation in the current mission of building and defending the nation.